Analisis Peran Organisasi Karang Taruna Dalam Meningkatkan Kesejahteraan Masyarakat Di Desa Gelam - Esti Maulida Apriliana; Wahyu Eko Pujianto (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This research explores the role of Karang Taruna in economic empowerment in Gelam Village through literature analysis.  Focus on the impact of Corporate Social Responsibility (CSR) programs and synergies with the private sector.  The findings present Karang Taruna's significant contribution in creating jobs, increasing access to financing, and strengthening the role of women.  Synergy with the private sector opens up market opportunities and knowledge transfer.  This study provides in-depth insight into economic empowerment strategies at the village level.